Brachydactyly mental retardation syndrome with growth hormone deficiency. (21st July 2018) - Arefzadeh, Alireza; Khalighinejad, Pooyan; Ataeinia, Bahar; Parvar, Pegah
Summary: Deletion of chromosome 2q37 results in a rare congenital syndrome known as brachydactyly mental retardation (BDMR) syndrome; a syndrome which has phenotypes similar to Albright hereditary osteodystrophy (AHO) syndrome. In this report, we describe a patient with AHO due to microdeletion in long arm of chromosome 2 [del(2)(q37.3)] who had growth hormone (GH) deficiency, which is a unique feature among reported BDMR cases. This case was presented with shortening of the fourth and fifth metacarpals which along with AHO phenotype, brings pseudopseudohypoparathyroidism (PPHP) and pseudohypoparathyroidism type Ia (PHP-Ia) to mind; however, a genetic study revealed del(2)(q37.3). We recommend clinicians to take BDMR in consideration when they are faced with the features of AHO; although this syndrome is a rare disease, it should be ruled out while diagnosing PPHP or PHP-Ia. Moreover, we recommend evaluation of IGF 1 level and GH stimulation test in patients with BDMR whose height is below the 3rd percentile. Learning points: Clinicians must have brachydactyly mental retardation (BDMR) syndrome in consideration when they are faced with the features of Albright hereditary osteodystrophy. Although BDMR syndrome is a rare disease, it should be ruled out while diagnosing PPHP or PHP-Ia. Evaluation of IGF1 level in patients diagnosed with BDMR whose height is below the 3rd percentile is important.